2019
DOI: 10.1001/jamaoncol.2018.7098
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Blood Tumor Mutational Burden as a Potential Biomarker for Immunotherapy in Patients With Non–Small Cell Lung Cancer With Use of a Next-Generation Sequencing Cancer Gene Panel

Abstract: This study explores whether blood tumor mutational burden estimated by a next-generation sequencing gene panel is associated with clinical outcomes of patients with non–small cell lung cancer treated with anti–programmed cell death 1 and anti–programmed cell death ligand 1 agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
315
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(342 citation statements)
references
References 23 publications
13
315
2
1
Order By: Relevance
“…For this reason, they compare TCGA WES-based TMB with panel-based TMB with or without inclusion of EGFR and/or KRAS mutations. Although similar results are yielded, the raised issue is an important point to be further investigated in panel-based TMB quantification [49]. TMB quantification from liquid biopsies suffers from ctDNA detection limits, which also depend on tumor size and number of cancer cells, but these results encourage to further explore and more extensively validate this approach.…”
Section: Tmb Quantification Beyond Tissue Biopsies and Current Gene Pmentioning
confidence: 63%
See 1 more Smart Citation
“…For this reason, they compare TCGA WES-based TMB with panel-based TMB with or without inclusion of EGFR and/or KRAS mutations. Although similar results are yielded, the raised issue is an important point to be further investigated in panel-based TMB quantification [49]. TMB quantification from liquid biopsies suffers from ctDNA detection limits, which also depend on tumor size and number of cancer cells, but these results encourage to further explore and more extensively validate this approach.…”
Section: Tmb Quantification Beyond Tissue Biopsies and Current Gene Pmentioning
confidence: 63%
“…As for synonymous mutations, it is claimed that, although not biologically meaningful, their inclusion may reduce sampling noise and improve the approximation of TMB across the whole genome. Indeed, several works compared TMB quantification with or without synonymous variants and observed that, when including synonymous variants, panel-based TMB shows increased correlation with WES-based TMB values [35,49] and stronger association with clinical response [9]. Starting from the [74] above observations, we can infer that some recommendations to build a standardized and robust analysis pipeline for TMB quantification are starting to emerge at least for the following points: i. germline variants can be most efficiently identified and removed by matched normal sequencing and, if this is not possible, the largest available germline variant databases should be used for in silico filtering, especially for non-caucasian ancestries; ii.…”
Section: Need For Standardization Of Tmb Quantification and Reportingmentioning
confidence: 99%
“…Recent studies have found that changes in plasma cfDNA concentration and bTMB in plasma cfDNA may be used as molecular biomarkers for predicting therapeutic effects in ICI therapy, 29,30 all of which support the exploration of immunotherapy-related molecular biomarkers based on liquid biopsy. 31 In the early study of small samples, it has been found that CTC PD-L1 expression can be detected in peripheral blood of tumor patients.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, the evaluation of tumor mutational burden (TMB), which is the number of somatic mutations in the genome coding regions (Mut/Mb), has been explored and is currently been tested in the cfDNA, to identify patients who can benefit from immunotherapy [99][100][101][102]. However, the first results on the concordance between tissue and cfDNA are contrasting [103].…”
Section: Resultsmentioning
confidence: 99%